2021
DOI: 10.12890/2021_002854
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected Pulmonary Embolism Late After Recovery from Mild COVID-19?

Abstract: SARS-CoV-2 infection is associated with an increased risk of venous thromboembolism (VTE), which is common during active illness but unusual in milder cases and after healing. We describe a case of bilateral acute pulmonary embolism occurring 3 months after recovery from a paucisymptomatic SARS-CoV-2 infection. The only VTE risk factor demonstrable was a history of previous SARS-CoV-2 infection, with laboratory signs of residual low-grade inflammation. Clinicians should be aware of VTE as a potential cause of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Currently, guidelines as well as experts’ opinions recommend the use of standard VTE thromboprophylaxis in all hospitalized patients who do not have suspected or confirmed VTE [ 5 , 6 , 7 ]. Nevertheless, many reports and investigations showed that a variable risk of COVID-19-associated VTE extends over the first 3 months after hospital discharge, but the cumulative incidence of such events has not been clearly determined [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ]. In this context, the American Society of Hematology (ASH) updated 2021 guidelines do not recommend extended anticoagulation in the COVID-19 patients discharged from the hospital, who do not have suspected or confirmed VTE, or another indication for anticoagulation [ 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, guidelines as well as experts’ opinions recommend the use of standard VTE thromboprophylaxis in all hospitalized patients who do not have suspected or confirmed VTE [ 5 , 6 , 7 ]. Nevertheless, many reports and investigations showed that a variable risk of COVID-19-associated VTE extends over the first 3 months after hospital discharge, but the cumulative incidence of such events has not been clearly determined [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ]. In this context, the American Society of Hematology (ASH) updated 2021 guidelines do not recommend extended anticoagulation in the COVID-19 patients discharged from the hospital, who do not have suspected or confirmed VTE, or another indication for anticoagulation [ 36 ].…”
Section: Introductionmentioning
confidence: 99%